2023
DOI: 10.35378/gujs.1090337
|View full text |Cite
|
Sign up to set email alerts
|

A literature review: Wind energy within the scope of MCDM methods

Abstract: Renewable energy sources are vital for environmental sustainability. With the damage of fossil fuels to nature and the depletion of fossil fuels over time, energy production from clean and inexhaustible renewable energy sources has become widespread. Wind energy, one of the renewable energy sources, is a clean energy source that does not emit any harmful waste to the environment. Wind energy is a low-cost energy source that is mostly used for electricity generation. Criteria such as wind speed, turbine structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…The main disadvantages of wind energy are high installation, maintenance, and operation costs, impact on the neighborhood, and low collecting power (Santos Júnior & Firmino, 2022;Eroğlu et al, 2023;Zarei & Ghaffarzadeh, 2023;Akinci et al, 2022). These disadvantages are financial and environmental.…”
Section: Disadvantages Of Renewable Energymentioning
confidence: 99%
“…The main disadvantages of wind energy are high installation, maintenance, and operation costs, impact on the neighborhood, and low collecting power (Santos Júnior & Firmino, 2022;Eroğlu et al, 2023;Zarei & Ghaffarzadeh, 2023;Akinci et al, 2022). These disadvantages are financial and environmental.…”
Section: Disadvantages Of Renewable Energymentioning
confidence: 99%
“…The most frequently used MCDM methods in the literature regarding wind farm siting solutions are the analytical hierarchy process (AHP) (e.g., [6,[9][10][11][12]), a technique for order of preference by similarity to ideal solution (TOPSIS) (e.g., [13][14][15][16][17]), VIKOR (e.g., [18][19][20]), elimination et choix traduisant la realité (ELECTRE) (e.g., [16,21,22]), and the preference ranking optimization method for enrichment evaluation (PROMETHEE) (e.g., [23,24]). In a recent study in which wind energy and MCDM methods were discussed, Eroglu et al [25] concluded that the AHP method is the most frequently used method.…”
Section: Introductionmentioning
confidence: 99%